Antioxidant Lotion Formulation with a Combination of Ethanol Extracts of Black Soybean and Pigeon Pea - Rekha Aulia Istikhomah; Rifkarosita Putri Ginaris; Alfina Nurrahman (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Indonesia’s tropical climate with high sun exposure increases the risk of oxidative stress on the skin due to free radicals. Synthetic antioxidants in skincare products are proven effective but may cause long-term side effects. Natural ingredients offer a safer and more promising alternative. This study aimed to formulate an antioxidant lotion using ethanol extracts of black soybean and pigeon pea. Extraction was carried out by maceration using 70% ethanol as solvent. The extracts were formulated into five lotion formulas, consisting of three extract combinations, one positive control, and one negative control. Evaluation included antioxidant activity using the DPPH method and physical stability tests. Formula 3, containing 11,31% black soybean extract and 3,75% pigeon pea extract, shows the highest antioxidant activity with a strong category (IC₅₀ = 73,5 µg/mL). All formulas show good physical stability during 21 days of storage and form oil-in-water emulsions. The combination of black soybean and pigeon pea extracts demonstrates strong antioxidant potential with good formulation stability and is suitable for development in natural cosmetic products.